Relational justice in the prophetic tradition: an analysis of selected hadith - Juliyana Junaidi; Latifah Abdul Majid; Mohd Arif Nazri (Penerbit Universiti Kebangsaan Malaysia, 2023)
Islam reveres justice as a paramount virtue that is explicitly commanded to permeate all spheres of human existence. The Quran commanded mankind to conduct justice. This commandment was subsequently assimilated and exemplified by the Prophet Muhammad through his prophetic traditions and serves as a crucial source that elucidates the concept of justice from an Islamic perspective. Acknowledging the significance of relational justice is imperative as it entails an understanding that justice encompasses more than just the equitable distribution of wealth, rights, and opportunities. Hence, the study aims to identify the dimensions of relational justice from the vantage point of the prophetic tradition, thereby serving as a moral compass for Muslims across a myriad of life’s dimensions. This qualitative study utilises document analysis in its data collection whereby the components of relational justice are first identified, followed by the recognition of related hadīth through the takhrīj process. Books of hadīth commentaries and other supporting sources are consulted while analysing the data to determine the reason behind the revelations, the people involved, and the locative and chronological factors. The findings of this study illustrate that relational justice from the Sunnah’s perspective encompasses various facets such as justice within the familial institution, inter-neighbourhood relations, and the dynamics between rulers and citizens. Consequently, the study posits that the Prophetic sunnah holds intrinsic potential to serve as a moral compass, warranting the promotion of justice across all realms of human endeavours.